(untitled) - Dam, J.T.P. van (Netherlands, 1996)
In a series of experiments the interaction between nutrition and energy- and nitrogen metabolism of West African Dwarf goats, infected with trypanosomes was studied. Animals were injected with trypanosomes, and feed intake, energy and nitrogen balance and blood metabolites and hormones were measured for a period of six weeks post infection. Trypanosoma vivax infection caused fever and anaemia.
Keywords: Dê,Goats; Chăn nuôi,Breeding